Архаичные черты в прологах Великого княжества Литовского - Чистякова, Марина Владимировна Владимировна (Slavistica Vilnensis, 2011)
Marina ChistiakovaArchaic Features in the Synaxaria of the Grand Duchy of LithuaniaThe article discusses some archaic features of Old Church Slavonic Synaxarion preserved in the relatively recent copies (15th–17th cc.) created and used in the Grand Duchy of Lithuania (University Library of the Catholic University of Lublin, nr. 198, 1584; Library of the Russian Academy of Sciences, 13.8.2, second half of the 16th c.; Vernadsky National Scientific Library of Ukraine, Kiev’s St. Sophia Cathedral collection, 273c/131, 1480’s; St. Michael’s Golden-Domed Monastery collection, nr. 529, 1480’s –1490’s et al.). These include the story about a transfer of relics (finger of the right arm) of John the Baptist from Constantinople to Kiev during the reign of Vladimir Monomakh (1113–1125); not expanded by didactic appeals patericon stories; a special version of the Tale of the murder of the Prince Gleb (4.IX) and some other features.